PERBANDINGAN POPULASI SERANGGA PERMUKAAN LANTAI HUTAN WANARISET, KALIMANTAN TIMUR - YAYUK RAHAYUNINGSIH SUHARDJONO (Research Center for Biology-Indonesian Institute of Sciences, 1985)
YAYUK RAHAYUNINGSIH SUHARDJONO. 1985. Berita Biologi 3 (3): 104 - 107. The study of insect fauna in the primary, secondary and swamp forest floor had been done in the Wanariset forest, East Kalimantan, during tije mid of dry season.September to October 1979. More than 18,000 specimens were collected by pit fall traps. This material consisted of 87 families belonging to 15 ordines. Based on the feeding habits of the insects caught during the study, 325% were phytophagous specks,29.07% predator-parasites, 20.93% decomposers and YIA undetermined species.The high density was shown by Entomobryidae, Sminttraridae and Fonrnkidae.